2005
DOI: 10.1086/499051
|View full text |Cite
|
Sign up to set email alerts
|

Neon Lights up a Controversy: The Solar Ne/O Abundance

Abstract: The standard solar model was so reliable that it could predict the existence of the massive neutrino. Helioseismology measurements were so precise that they could determine the depth of the convection zone. This agreement between theory and observation was the envy of all astrophysics -until recently when sophisticated three-dimensional hydrodynamic calculations of the solar atmosphere reduced the metal content by a factor of almost two. Antia & Basu (2005) suggested that a higher value of the solar neon abund… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
70
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 24 publications
16
70
0
Order By: Relevance
“…These results confirm those of λ And and V851 Cen (Sanz-Forcada et al 2004), displayed here for easier comparison (Fig. 7 "solar model problem" (see also discussion in Schmelz et al 2005). The ratios in the coronae of AR Psc and AY Cet are consistent with the value observed by Drake & Testa (2005).…”
Section: Resultssupporting
confidence: 88%
“…These results confirm those of λ And and V851 Cen (Sanz-Forcada et al 2004), displayed here for easier comparison (Fig. 7 "solar model problem" (see also discussion in Schmelz et al 2005). The ratios in the coronae of AR Psc and AY Cet are consistent with the value observed by Drake & Testa (2005).…”
Section: Resultssupporting
confidence: 88%
“…Briefly, Asplund et al (2005) inferred from improved models for the solar atmosphere that the solar oxygen and carbon abundances were much lower than thought previously. The revised abundances, however, led to discrepancies between helioseismology and models for the solar interior (e.g., Schmelz et al 2005). To remedy this, it has been suggested that the abundance of neon might have to be revised upwards (e.g., Bahcall et al 2005), but this leads to a number of other problems (e.g., Young 2005;Drake & Testa 2005).…”
Section: Resultsmentioning
confidence: 99%
“…This solution seemed to be particularly promising, since Drake & Testa (2005) found that most neighboring stars seem to have a much higher Ne/O ratio than the Sun. However, Schmelz et al (2005) and Young (2005) reanalyzed solar X-ray and UV data, respectively, to find that the Ne/O ratio of the Sun is indeed consistent with the old lower value. Interestingly, recent measurements by Ayres et al (2006), using the CO lines from a combination of data from the shuttle-borne Atmospheric Trace Molecule Spectroscopy (ATMOS) Fourier transform spectrometer and groundbased observations yields an oxygen abundance that is much higher than the recent ASP value and close to that of GS.…”
Section: Introductionmentioning
confidence: 91%